Introducing public relations : theory and practice - Butterick, Keith (London, UK : SAGE, 2011)
Introducing Public Relations is your guide to the basics of public relations: where it came from, what it means and what issues the industry faces today. It takes readers from the origins of PR all the way to the newest theoretical debates, explaining along the way the changes and development of the role of the PR practitioner. With interviews and 'day in the life' examples from a wide range of professionals in the industry students will learn what PR practitioners do, what they think and how the industry really works. Putting the student first, this book: Gives a grounded, critical coverage.
Includes bibliographical references and index.
BSBA
Keywords: Public relations